Increased frequencies of Th17 cells and IL17a-producing regulatory T-cells preceding the immunodiscordant response to antiretroviral treatment. Issue 1 (January 2018) - Rosado-Sánchez, Isaac; Herrero-Fernández, Inés; Tarancon-Diez, Laura; Moreno, Santiago; Iribarren, Jose Antonio; Dalmau, David; Vera-Méndez, Francisco; Leal, Manuel; Pacheco, Yolanda María
Highlights: Increased Th17 frequency and IL17a-cytokine-combinations precede immunodiscordance. Increased IL17a-producing Treg frequency precedes immunodiscordance. Though increased both cellular subsets, no alteration in Treg/Th17 ratio precedes immunodiscordance. Summary: Background: Despite the fact that antiretroviral therapy (cART) suppresses HIV-viremia, an adequate CD4 T-cell recovery is not always achieved (immunodiscordant response to cART). IL17a-producing CD4 T-cells (Th17) constitutes an important subset involved in the preservation of mucosal surfaces integrity, which depletion has been associated with disease progression in HIV-infection. However, whether Th17 frequency at cART initiation is associated with a poor CD4 T-cell recovery has not been yet explored. Our aim was to explore whether the Th17 cells and other IL17a-producing T-cell subsets at cART initiation were associated with a subsequent immunodiscordant response to cART. Methods: We selected pre-cART samples of antiretroviral-naïve subjects with and without a low CD4 recovery after cART (LR-subjects and HR-subjects, respectively). Peripheral blood mononuclear cells (PBMCs) were stimulated with PMA/ionomycine, and the production of several cytokines including IL17a was analyzed by flow cytometry. Results: A trend to higher Th17 ( p = 0.05) and increased frequencies of IL17a-producing Treg ( p = 0.011) was found in LR-subjects before cART onset. Despite increased frequencies of both Treg and Th17 in LR-subject at cART initiation, no alteration of Treg/Th17 ratio was observed. While polifunctional profile of CD4 T-cells was not different, frequencies of CD4 T-cells producing cytokine-combinations including IL17a were increased in LR-subjects. Conclusion: Increased frequencies of Th17, IL17a-producing Treg and CD4 T-cells producing specific IL17a-containing combinations of cytokines, precede the immunodiscordant response to cART, suggesting a potential contribution of these subsets in such anomalous response to cART.